Efficacy of a polyherbal formulation in PCOD: A prospective clinical trial (Indian Journal of Traditional Knowledge (IJTK), 2026)
Polycystic ovarian disease (PCOD) is one of the most common endocrine disorders affecting women of reproductive age worldwide, with a prevalence of 5–15% depending on diagnostic criteria. Its aetiology involves genetic and environmental factors. Clinically, PCOD presents with hyperandrogenism, oligomenorrhoea, anovulation, and polycystic ovarian morphology. Due to the limitations and side effects of conventional therapies, there is increasing interest in alternative and holistic approaches. This study aimed to evaluate the efficacy of a Unani polyherbal formulation in the clinical management of PCOD. A pre–post interventional clinical study was conducted on 30 women aged 18–35 years diagnosed with PCOD based on ESHRE/ASRM criteria. Patients with pelvic pathology, malignancy, uncontrolled diabetes, hypertension, thyroid disorders, or those using contraceptives were excluded. Participants received a formulation comprising Nankhawah, Badiyan, and Wajturki, administered orally twice daily for five days before the expected menstrual period and continued for five days, for three consecutive cycles. Outcome measures included ovarian volume, menstrual cycle duration, body weight, acanthosis nigricans (AN) score, modified Ferriman–Gallwey (mFG) score, and SF-12 quality of life. Statistically significant improvements were observed post-treatment (p